Administration of lidocaine 2% in endodontic treatment of irreversible pulpitis case of right lower back tooth: Pemberian lidokain 2% pada perawatan endodontik kasus pulpitis irreversibel gigi belakang bawah kanan - Hasanah, Nisrina Rufaidah; Nurdin, Denny (Makassar Dental Journal, 2025)
Irreversible pulpitis and root canal treatment (RCT) are conditions that can cause pain. Local anaesthesia is one of the ways to manage pain. However, pulpitis patients often experience anaesthetic failure despite using various types of anaesthetic agents. A 32-year-old woman came to RSGM Unpad with complaints of a large hole in the right lower back tooth. The examination showed that tooth 45 had asymptomatic irreversible pulpitis with normal apical tissue so it was necessary to do RCT. Before treatment, the patient was anaesthetised with buccal and intrapulpal infiltration using lidocaine 2%, epinephrine 1:80,000. It was concluded that the administration of 2% lidocaine epinephrine 1:80,000 before RCT in a patient with AIP performed quickly, efficiently, without any side effects. During treatment, the patient did not complain of pain and comfortably accepted each stage of treatment.